The use of armed drones against State actors: The killing of General Soleimani in Iraq - Raquel Regueiro Dubra (Behavior & Law Journal, 2025)
This study analyses the lawfulness of the targeted killing of General Qasem Soleimani in Iraq by a U.S. armed drone on January 2, 2020. As the United States of America provided different justifications for the strike against Soleimani, this article assesses the lawfulness of unmanned aerial vehicles and the legal justifications for the killing under ius in bello and ius ad bellum: the existence of an ongoing international armed conflict between the United States and Iran that would make Soleimani a legitimate military target; the possible consent of the territorial State to the military action, and the lawfulness of the invocation of the exercise of self-defense by the United States against Iran due to previous armed incidents. This case highlights the challenges in justifying targeted killings under International Law as their extrajudicial nature raises concerns about their legitimacy under International Humanitarian Law and the right of self-defense is of no use when a State fails to demonstrate the existence of an ongoing armed attack or its imminence.